Survey on Treatment-Seeking Patterns in Patients With Allergic Rhinitis - Gwanghui Ryu; Do Hyun Kim; Chang Yeong Jeong; Sang Min Lee; Il Hwan Lee; Soo Whan Kim; Hyeon-Jong Yang; Mi-Ae Kim; Dong-Kyu Kim (Journal of Rhinology)
Background and Objectives The medications preferred by patients for allergic rhinitis and their usage remain unclear. This study investigated treatment-seeking behaviors in patients with allergic rhinitis, including medical treatments, environmental controls, and surgical treatments. Methods In this study, a cross-sectional survey was conducted by internal medicine, pediatric, or otorhinolaryngology physicians at university hospitals from January 2022 to April 2022. A questionnaire was administered to patients with confirmed allergic rhinitis to collect information regarding medical treatments (prescription and over-the-counter medication use patterns, comorbid asthma, and allergen-specific immunotherapy), environmental controls (usage of air purifiers and pet avoidance), and experiences with surgical treatments. Results We included 51 patients with allergic rhinitis with a mean age of 31.6±16.0 years. Among them, 47 (92.2%) and 6 (11.8%) patients had pollen allergies and asthma, respectively. Furthermore, 41 (80.4%) patients took prescribed medicines, while 39 (76.5%) patients only used the medication when experiencing symptoms. Thirty patients (58.8%) reported concurrent use of intranasal sprays and oral medications. Thirty-three patients (64.7%) reported awareness of immunotherapy, and there were no preferential differences between subcutaneous (52%) and sublingual immunotherapy (48%). Of the 36 patients (70.6%) who reported using an air purifier, 38.9% considered it helpful in preventing allergic rhinitis symptoms. Fourteen patients (27.5%) currently or previously had a companion animal, with half experiencing worsening of symptoms. Twelve patients had received surgical treatment and reported high satisfaction levels (41.6%, very satisfied; 41.6%, satisfied). Conclusion Patients with allergic rhinitis showed similar preferences for oral and spray medications. They also showed satisfaction with surgical treatments and an interest in the environmental management of allergic rhinitis.